Late Eocene-Pleistocene Planktonic Foraminiferal Biostratigraphy of the Kuripan-1 Well, North Central Java, Indonesia - Darwin Kadar; Ricky Adi Wibowo; Hansen Wijaya; Leonardo Sebayang; Emma Yan Patriani (Ikatan Ahli Geologi Indonesia, 2014)
Planktonic foraminifera of the Kuripan-1 well, North Central Java, Indonesia were studied in detail, using side wall cores collected from the marine Ngimbang, Kujung, Tuban, Selorejo and Lidah Formations. The age interpretation, using first and last appearance datum planes. concludes that the well section ranges in age from Late Eocene to Pleistocene (upper Zone P17- Zone N22 of Blow, 1969). The main datum planes, from old to young, are Globigerina gortanii(B), Globigerina sellii(B), Globigerina angulisuturalis(B), Globigerinoides primordius(B), Globorotalia kugleri(T), Praeorbulina sicana(B), Orbulina suturalis(B), Globorotalia peripheroronda/G.praefohsi(T) and Globorotalia tosaensis(B).The Ngimbang Formation is likely Late Eocene in age and the Kujung Formation ranges from latest Eocene(?) to earliest Miocene (upper Zone P17- lower N4). The Selorejo and Lidah Formatons are likely Late Pliocene to Pleistocene in age. The zonation also shows the presence of a late Middle Miocene- Early Pliocene hiatus between the Tuban and the overlying Selorejo Formation, spanning zones N13- N19, which reflects a Late Miocene uplift event in the Rembang zone.A chronostratigraphic correlation between the Kuripan-1 and the Purwodadi-1 wells is attempted using some of the above datum planes, as well as other bioevents occurring in both wells. The correlation of the two wells indicates that the Late Miocene hiatus in Kuripan-1 is correlatable with the top of the Tuban Formation in Purwodadi-1. The Prupuh limestone, above the Globigerina sellii top datum in Purwodadi 1, is not developed in Kuripan-1. Here, the carbonate facies changes to a mudstone of shallow marine environment. The upper Ngimbang and Kujung Formations in Kuripan-1, bounded at the top by the Top Globigerina sellii datum and at the base by the Top Globorotalia centralis datum, is well correlated with the upper Ngimbang and Kujung Formations in the Purwodadi-1 well.